KH. AHMAD HANAFIAH PEJUANG KEMERDEKAAN INDONESIA ASAL KARESIDENAN LAMPUNG - Johan Setiawan; Aman Aman (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This research inteded to find the biography of KH. Ahmad Hanafiah and to examine his fight in haslling the Independent of Indonesia in Karesidenan Lampung. The methode of this research was historic method by using steps, (1) heuristics, (2) resource critics, (3) interpretations, (5) historiography. Derivying the result from the instruments, it can be drawn as follows; (1) KH. Ahmad Hanafiah was a clergy and a religion teacher who served himself as the politician or a teacher in Lampung region. (2) KH. Ahmad Hanafiah was a leader of Sukadana Hisbullah Troops whom sacrifice himself in facing the first Netherland Military Agression and he was died in the battlefield in 1947.Keywords: KH. Ahmad Hanafiah, Patriotist, Lampung Region